Helical dislocations: Observation of vacancy defect bias of screw dislocations in neutron irradiated Fe–9Cr. (December 2019) - Haley, J.C.; Liu, F.; Tarleton, E.; Cocks, A.C.F.; Odette, G.R.; Lozano-Perez, S.; Roberts, S.G.
Abstract: We have analysed the microstructure of a model alloy of Fe9Cr irradiated with neutrons to a dose of 1.6 dpa at 325  °C. Helical dislocations comprise a major part of the damage; these formed from the interaction of pre-existing screw dislocations with irradiation-induced defects. We have investigated the process behind how these helices form, and how they cause local clustering of dislocation loops. Specifically, we have shown experimentally that the interaction of vacancy defects with pre-existing screw dislocations causes the formation of mixed screw-edge helical dislocations. Interstitials and vacancies were generated in equal numbers, which shows that the screw dislocations must have acted as vacancy-biased sinks. Helical dislocations in general were analysed from a theoretical perspective, and three Dimensional Discrete Dislocation Dynamics (3D-DDD) was used to develop a model for the formation and growth of a vacancy-fed helical dislocation. Since the helical dislocations cause the removal of vacancies from the local microstructure, this leaves a higher supersaturation of interstitials close to the dislocations. We argue that this supersaturation is responsible for enhanced interstitial loop coarsening, leading to a higher proportion of visible interstitial clusters in the vicinity of helical dislocations. These findings offer a new perspective on how dislocations affect the spatial homogeneity of radiation damage. Graphical abstract: Image, graphical abstract